Inventory of fine particulate organic compound emissions from residential wood combustion in Portugal - Gonçalves, Cátia; Alves, Célia; Pio, Casimiro (Atmospheric Environment, 2012)
In the early fall of 2010 a survey questionnaire was conducted to assess residential wood combustion (RWC) practices in the 18 districts of mainland Portugal. This paper describes and analyses the results from a bottom-up approach, based on this telephone survey, which enabled the characterisation of RWC practices in each district. Additionally, emission factors and source proﬁles obtained from different RWC tests, allowed the estimation of CO, CO2, PM2.5 and particulate organic compound emissions on a country-scale. The type and number of RWC appliances, each with their speciﬁc emissions factor and the amount and type of fuel used vary signiﬁcantly on a district scale. The energy consumption in RWC appliances was estimated to be 35 342 TJ y 1 . The estimated emissions of PM2.5 from RWC in Portugal (10.96 kt y 1 ) represent 30% of the estimate for different source activities reported in a recent inventory. The national emissions of OC and EC were estimated to be 5.32 and 0.53 kt y 1 , respectively. It was also estimated that the total CO2 emissions from RWC in Portugal are 1.7 Mt y 1 . The levoglucosan emissions contribute with between 7.8% and 16.1% of PM2.5 emissions from RWC
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Burning appliances; Emission factors; Inventory; survey questionnaire; Wood species